Postural Syncope and Constipation: An Unusual Presentation of a Duodenal Dieulafoy's Lesion. (7th March 2017) - Dirweesh, Ahmed; Chikezie, Alvarez; Khan, Muhammad Yasir; Zia, Sana; Tahir, Muhammad
Abstract : Dieulafoy lesions are a rare etiology of gastrointestinal bleeding from a large caliber-persistent tortuous submucosal artery. They account for 1-2% of all causes of acute gastrointestinal hemorrhage with 80%–95% of these lesions located in the stomach along the lesser curvature. One-third of these lesions present at an extragastric location, with the proximal duodenum accounting for 15% of them. We present a 21-year-old male with no significant past medical history or risk factors, who presented with repeated syncopal episodes followed by hematemesis, found to have a Dieulafoy lesion located at the duodenal bulb. This lesion was diagnosed and successfully treated via upper endoscopy with epinephrine injection and the application of 2 endoscopic clips.